Sex difference in the expression of PD-1 of non-small cell lung cancer - Gu, Yong; Tang, Ying Y.; Wan, Jian X.; Zou, Jian Y.; Lu, Chuan G.; Zhu, Hao S.; Sheng, Si Y.; Wang, Yan F.; Liu, Hai Ch.; Yang, Jia; Hong, Hai (Frontiers in Immunology, 2022)
Evidence increasingly indicated that lung cancer incidence in female individuals continue to rise, and women have a higher risk to develop adenocarcinoma than men. Male and female individuals differ in their innate and adaptive immune responses, and there are sex differences in response to the PD-1/PD-L1-dependent blocking immunotherapy. Whether the differential expression of PD-1 between genders affect the response to blocking treatment is currently unknown. In this study, we examined sex differences in serum sPD-1, mPD-1 expression on T cells, and sex hormone levels in non-small cell lung cancer (NSCLC) patients. Our results revealed a higher level of sPD-1 and expression of PD-1 on CD4+T cell in female patients than in male patients; we identified that serum sPD-1 level and the expression of mPD-1 on T cells were significantly reduced in NSCLC; we also found that serum testosterone level increased in female patients compared with control subjects and that increased testosterone downregulated the expression of mPD-1 on T cell. These findings provide a better understanding of the differences in PD-1 expression between genders in NSCLC patients and the effect of sex hormones on PD-1 expression and supply evidence for early lung cancer diagnosis and responsiveness to immune checkpoint inhibitors.